Immune Modulation in the Treatment of Amyotrophic Lateral Sclerosis: A Review of Clinical Trials - Khalid, Syed I.; Ampie, Leonel; Kelly, Ryan; Ladha, Shafeeq S.; Dardis, Christopher (Frontiers in Neurology, 2017)
Amyotrophic lateral sclerosis (ALS) is a progressive neurodegenerative disease characterized by the degeneration of motor neurons. Though many molecular and genetic causes are thought to serve as predisposing or disease propagating factors, the underlying pathogenesis of the disease is not known. Recent discoveries have demonstrated the presence of inflammation propagating substrates in the central nervous system of patients afflicted with ALS. Over the past decade, this hypothesis has incited an effort to better understand the role of the immune system in ALS and has led to the trial of several potential immune-modulating therapies. Here, we briefly review advances in the role of such therapies. The clinical trials discussed here are currently ongoing or have been concluded at the time of writing.